The Effect of Urban Street Planting on Improving the Climate of Baghdad city - Miqdad Haidar Al-Jawadi; Ali Hussain Al-Bayati (Iraqi Journal of Architecture and Planning, 2018)
The aim of this research is to study the effect of tree planting on the reduction of thermal load of solar radiation falling on the area of Baghdad city and its contribution to weather treatments; since the temperature of green mass of trees is less than the human body and higher than air temperature in winter, so one expects condense tree plantation and foliage may participate in reducing air temperature in summer and could make the climate of the city to approach near the human temperature comfort limits .The impetus to encourage the authors to undertake the research is the positive results and indications derived from earlier authors' research work and that done by other researchers. Recent advances of modern scientific and technological in the field of electronic instrumentation measurements and sophisticated thermal imaging devices, which are expected to help in measurement and obtain temperature pattern of every point on the trees or at any point on block trees, besides measuring the thermal effect of shading on human body of people using the road (the camera has an accuracy of (0.1 oC).In order to ensure high precision and optimum reliability of experimental results in the proposed work, experts from the College of Agriculture, University of Baghdad were approached to assist in selecting one of the best suitable tree for Baghdad environment. Their choice was ( Albizia Lebbech ), and by the use of (GIS) photos of Baghdad city, the most suitable site to perform the experimental measurements in Baghdad city is chosen as the Baghdad University, in view of abundance of Albizia in addition to the availability of all other required variables. With the kind permission of the Presidency of Baghdad University, experiments have been performed on the 21st of June 2012, since this day has the highest amount of solar radiation all over the year The results and analysis have shown that there is a distinct effect of shading with trees in reducing temperature street air temperature and in providing better human effective temperature than shading the walkways with buildings . In an attempt to theoretically verify the extent of this impact on the entire city of Baghdad calculated, only the whole length of the main streets of Baghdad city are found by satellite images "GIS" ( within the boundaries of Municipality of Baghdad). It shows that the forestation process, including the effect of shading and evaporative cooling is equivalent to 45 million tones of refrigeration, which certainly will help in reducing the required energy for buildings' cooling . Therefore, the results will encourage in recommending forestation over all main streets as well as all streets in residential districts, which in return will change the whole climate of the city of Baghdad.Key words: planting trees, thermal comfort, energy consumption, shade and